Comparison of Antioxidant Activity of Cichorium intybus by Using Different Reported Antioxidant Assays - Riaz*, Sadaf; Ullah Khan, Islam; Zahid Qurashi, Muhammad; John, Peter; Ul Hassan, Mukhtar; Kausar, Rukhsana; Ali Rana, Faraz; Sohail, Maria (Asian Journal of Chemistry, 2011)
Present work reports in vitro antioxidant and radical scavenging capacity of different organic and inorganic fractions of Cichorium intybus which are effective for the curing of liver disorders, gallstones and infection of the urinary tract. These are the traditionally used herbs against degenerative diseases so it is an important task to evaluate their antioxidant activity. Extraction of herb was carried out in aqueous as well as in different organic solvents. Antioxidant activity and radical scavenging potential of the seven fractions were studied by using different antioxidant assays such as ABTS 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid), FRAP (ferric reducing antioxidant power), TPC (total phenolic contents), DMPD (N,N-dimethyl-p-phenylene diamine) and DPPH (diphenyl-1-picrylhydrazyl) radical scavenging assay. Trolox equivalent antioxidant activity (TEAC) of the aqueous and organic fraction of these herbs was determined by calculating the percentage inhibition of the coloured radical solution after reaction with sample and standard antioxidants by comparing with the standard curve formed by trolox as standard antioxidant. Ferric reducing antioxidant power and TPC decolourization assays, C. intybus showed a wide range of antioxidant activity. Using total phenolic content assay the amount of total phenolics components for different fractions of C. intybus ranged from 0.465-4.807 μM and ferric reducing antioxidant power assay TEAC values ranged from 1.013-6.133 μM which showed the presence of many antioxidant components in composition.